Campylobacter coli in Swine Slaughtering Flowchart and Research of cdt Genes - Milan, Camile; Moraes, Thamíris Pereira de; Ferrasso, Marina de Mattos; Ebersol, Celina Nunes; Neto, Amilton Clair Pinto Seixas; Silva, Éverton Fagonde da; Timm, Cláudio Dias (Acta Scientiae Veterinariae, 2017)
Background: Campylobacter spp. are among the microorganisms most commonly associated with foodborne disease. Campylobacter spp. isolation from pigs during the slaughter and final products have been reported in several countries, including Brazil. However, very little is known about the sources of contamination in the slaughtering flowchart and how these microorganisms are spread in processing plants. Considering the possibility of the pigs carry Campylobacter spp. since the farm or its products are contaminated in the slaughterhouse, this study had as aim to track Campylobacter spp. in pig slaughtering flowchart to understand the behavior of these pathogens in the production line. Materials, Methods & Results: Forty animals of 10 lots, four from each lot, were followed during slaughter. Stool samples were collected from the floor of each enclosure where the pigs were housed on the farm and immediately after stunning on slaughterhouse. Samples from carcass surface were collected after removal of the animals from scrap machine, after evisceration and before the refrigeration chamber. It was also collected surface samples from jowls and samples from the scalding tank water before and after the passage of animals. The swabs containing samples were plated onto Columbia agar supplemented with activated charcoal, oxygen reduction solution and antibiotics supplement, and incubated at 42°C for 48 h under microaerobic conditions. The colonies which presented with a shiny and moist appearance were analyzed by Gram staining for identification of Campylobacter by morphology, and then tested for catalase and oxidase. The Campylobacter isolates were identified for species C. jejuni or C. coli by PCR. Bands profiles were determined by rep-PCR and used to compare the strains. Campylobacter was isolated from 19 (9.5%) of the 200 pig samples analyzed, seven (36.8%) of the rectum, seven (36.8%) after evisceration and five (26.3%) before the refrigeration chamber. Campylobacter was not isolated from jowls and from scalding tank water. All isolates were C. coliand cdtnegative.Persistence of strains originating from the farm and cross contaminations during the slaughtering flowchart was identified by the analysis of the bands profiles obtained by rep-PCR. Discussion: C. coli was the species of Campylobacter present in the swine intestinal tract and in the swine slaughterhouse. The animals, once contaminated, can carry the microorganism during the stages of the slaughtering flowchart. The farm where the animals came from is an important source of contamination during processing, however cross contamination also plays a relevant role. The evisceration was considered the most critical stage, due to the greater number of isolates obtained after this procedure, what emphasize the importance of the hygienic-sanitary management in this stage. Campylobacter spp. can survive, despite not being able to multiply, in foods at refrigeration temperatures (-1 to 5°C) for one to three weeks. Therefore, the high percentage of isolates obtained from the carcass before the refrigeration chamber may represent a problem, since the contamination of the carcasses that enter in this sector can be maintained until the food reaches the consumer. There was no similarity between strains isolated from different lots, indicating that there were no persistence of strains both in the farm and in the slaughterhouse.